Association study of transition of laboratory marker levels and transition of disease activity of atopic dermatitis patients treated with dupilumab. (15th September 2021) - Mizuno, Maki; Horiguchi, Go; Teramukai, Satoshi; Ichiyama, Susumu; Ito, Michiko; Hoashi, Toshihiko; Kanda, Naoko; Saeki, Hidehisa
Abstract: Background: Dupilumab, a fully human monoclonal antibody that blocks signalling pathways of interleukin (IL)‐4 and IL‐13, is effective in treating patients with atopic dermatitis (AD). We previously showed that transitions of serum thymus and activation‐regulated chemokine (TARC) levels and eosinophil numbers were strongly associated with that of AD activity and that the transitions of serum lactate dehydrogenase (LDH) and immunoglobulin E (IgE) levels were weakly and not associated with that of AD activity, respectively, in patients treated without dupilumab. Objectives: The purpose of this study was to elucidate whether the association of the transition of laboratory marker levels and transition of disease activity in dupilumab‐treated AD patients (present study) was different from that in patients who are not treated with dupilumab (previous study). Methods: Sixty AD outpatients treated with dupilumab were included in this study. Associations between the transition of the eczema area and severity index (EASI) score and those of above‐mentioned laboratory marker levels were evaluated using a mixed effects model of EASI as the response variable, laboratory markers as fixed effects and patients as random effects. Results: The transitions of serum TARC and LDH levels were associated strongly with that of AD activity, but the transitions of serum IgE level and eosinophil numbers were associated with that of AD activity intermediately and weakly, respectively. Conclusions: Laboratory markers are useful for evaluating the effects of treatments for AD, but the meaning of each laboratory marker depends on the drugs used for treatment.